INTEGRATING SUSTAINABLE DEVELOPMENT INTO EDUCATION: STRATEGIES FOR TRANSFORMING CURRICULUM AND PRACTICE - Suchita Aggarwal; Ramnita Saini Sharda (Cirebon International Conference on Education and Economics Proceeding, 2024)
This paper explores the pivotal role of education in fostering sustainable development. Education is defined not only as the acquisition of knowledge but as a process of self-development that enhances understanding, consciousness, and capabilities. Given the unsustainable trends of current advancements, the paper emphasizes the need for education to address and integrate sustainability principles. It argues that education should provide the necessary awareness and training to shape the minds of youth towards sustainability. The paper highlights how educators and educational institutions can evolve into essential tools for achieving sustainability by incorporating sustainable development practices into their curricula. It offers practical solutions for how institutions can integrate waste management and sustainable practices into their operations, thereby setting a tangible example for students and inspiring a broader cultural shift towards sustainability.